Larvicidal, Repellent, and Irritant Potential of the Seed-Derived Essential oil of Apium graveolens Against Dengue Vector, Aedes aegypti L. (Diptera: Culicidae) - Kumar, Sarita; Mishra, Monika; Wahab, Naim; Warikoo, Radhika (Frontiers in Public Health, 2014)
Aedes aegypti L., the primary carrier for viruses causing dengue, chikungunya and yellow fever is widespread over large areas of the tropics and subtropics. Keeping in view the adverse effects of chemical insecticides-based intervention measures; the eco-friendly, bio-degradable essential oil extracted from the seeds of celery, Apium graveolens; was investigated for anti-mosquito potential against Ae. aegypti. Evaluation of larvicidal potential of celery seed oil against early fourth instars of Ae. aegypti resulted in LC50 and LC90 values of 16.10 ppm and 29.08 ppm, respectively, after an exposure to 24 h; the toxic effect of the oil increasing by 1.2 fold with an LC50 value of 13.22 ppm after an exposure to 48h. Interestingly, the seed oil did not cause rapid mortality, suggesting a delayed type of larval killing effect. The remarkable finding of the present study was effective repellency of the essential oil leading to 100% protection till 165 min as compared to control that did not show any repellency against mosquitoes. Only 1 bite was recorded in the 165th minute after which only 2 bites were scored until 180 min of exposure of the oil to the adult mosquitoes. An exciting observation was the knocked-down of mosquitoes caused by the exposure to 10% oil-impregnated papers. The exposure to 1% oil resulted in first flight only after 4 sec and a total of 63.66 average flights during 15 min exposure revealing the relative irritability of 26.97.The qualitative phytochemical study of the oil showed the presence of terpenoids, lactones and flavonoids as the major constituents suggesting their possible role in the toxicity. Present investigations proved celery seed essential oil to be an efficient larvicide and repellent against dengue vector. Further studies are needed to identify the active principles involved, their mode of action, formulated preparations for enhancing potency and stability, toxicity and effects on non-target organisms and the environment.